1991
DOI: 10.1088/0268-1242/6/6/017
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the negative charge state of DX centres in AlxGa1-xAs:Si

Abstract: We study here t h e thermally activated capture of electrons on Si-induced impurity states (DX centres) in AI,Ga,.,As ( x = 0.28 and 0.33) after photoionization at low temperature (6. 5-160 K) and under pressure ( C M kbar). We show that the combination of isothermal and thermostimulated experiments under pressure permits u s to state that the capture rates onto the different configurations of the DX centre related to the local environment of the donor atom in the AI,Ga,_,As alloy are not very different from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The emission parameters and the level's separation were the same as used in calculations for x = 0.15, but the level's ladder was pushed down into the gap by taking Eo,, = -120 meV. The simulated PPC recovery dependence n(Q, shown in figure 9, exhibits characteristic step-like structure, which was in fact observed experimentally [5- 7,9]. The evolution ofelectron population on individual DX levels is similar to that found in the x = 0.15 case.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…The emission parameters and the level's separation were the same as used in calculations for x = 0.15, but the level's ladder was pushed down into the gap by taking Eo,, = -120 meV. The simulated PPC recovery dependence n(Q, shown in figure 9, exhibits characteristic step-like structure, which was in fact observed experimentally [5- 7,9]. The evolution ofelectron population on individual DX levels is similar to that found in the x = 0.15 case.…”
Section: Resultsmentioning
confidence: 79%
“…I t was assumed that these occupancies corresponded approximately to the equilibrium distribution at 140 K, 'frozen' when the sample was cooled under pressure. This means that the energies shown in figure 6 as a function of pressure relate to 140 K. The thermal shift of two levels DX, and DX,, equal to 0.37 meV K-', was found by fitting the model n (7) dependences to the experimental results shown in figure 1 (it was assumed that both levels have the same temperature coefficient). Similar calculations of the level's positions were performed for the positive-Cl (Do) case.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of a recent experiment using deep-level transient spectroscopy on samples co-doped with germanium and silicon showed that DX centres associated with the Ge atoms bound two electrons [18], and Mossbauer measurements on Sndoped GdAs have been interpreted as showing that two or three electrons are localized at each DX centre [19]. Recent interpretations of thermal capture and emission kinetics data of DX centres have been shown to be consistent with a negatively charged DX centre but not ' Local vibrational mode spectroscopy of DX centres with a neutral DX centre [20,21]. Studies of the change in mobility caused by a DX transformation should also help determine if these defects are charged or neutral, but the interpretation ofexisting data has not led to definitive conclusions [22-241.…”
Section: Introductionmentioning
confidence: 99%